Primary Myelofibrosis in a Young Girl- A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Myelofibrosis (MF) is a rare disorder that is classified as one of the myeloproliferative disorders. It is a BCR-ABL1- negative myeloproliferative neoplasm characterized by abnormal proliferation of hemopoietic stem cells within the bone marrow, which leads to overproduction of fibrous tissue. Our patient a young girl of 17 year old presented with lump in left upper abdomen, shortness of breath & generalized swelling. The diagnosis was made based on severe anaemia, pancytopenia in peripheral blood film. Bone marrow trephine biopsy from the tibia revealed myelofibrosis. Splenectomy was done in an attempt to reduce the total volume of malignant cells and improve the features of hypersplenism. Myelofibrosis with hypersplenism in a 17- year- old girl is reported rarely. However, when it does, it usually runs rapid and fatal course.J Bangladesh Coll Phys Surg 2023; 41: 239-243